Giving birth on the way to the clinic: undocumented migrant women's perceptions and experiences of maternal healthcare accessibility along the Thailand-Myanmar border - Naomi Tschirhart; Wichuda Jiraporncharoen; Chaisiri Angkurawaranon; Ahmar Hashmi; Sophia Hla; Suphak Nosten; Rose McGready; Trygve Ottersen (BMC, 2023)
Abstract Background Millions of women give birth annually without the support of a trained birth attendant. Generally and globally, countries provide maternal health services for their citizens but there is a coverage gap for undocumented migrant women who often can't access the same care due to their legal status. The objective of this investigation is to explore undocumented migrants' experiences and perceptions of maternal healthcare accessibility. Methods We held focus groups discussions with 64 pregnant women at 3 migrant health clinics on the Thailand-Myanmar border and asked how they learned about the clinic, their health care options, travel and past experiences with birth services. In this context undocumented women could sign up for migrant health insurance at the clinic that would allow them to be referred for tertiary care at government hospitals if needed. Results Women learned about care options through a network approach often relying on information from community members and trusted care providers. For many, choice of alternate care was limited by lack of antenatal care services close to their homes, limited knowledge of other services and inability to pay fees associated with hospital care. Women travelled up to 4 h to get to the clinic by foot, bicycle, tractor, motorcycle or car, sometimes using multiple modes of transport. Journeys from the Myanmar side of the border were sometimes complicated by nighttime border crossing closures, limited transport and heavy rain. Conclusions Undocumented migrant women in our study experienced a type of conditional or variable accessibility where time of day, transport and weather needed to align with the onset of labour to ensure that they could get to the migrant clinic on time to give birth. We anticipate that undocumented migrants in other countries may also experience conditional accessibility to birth care, especially where travel is necessary due to limited local services. Care providers may improve opportunities for undocumented pregnant women to access maternal care by disseminating information on available services through informal networks and addressing travel barriers through mobile services and other travel supports. Trial registration The research project was approved by Research Ethics Committee at the Faculty of Medicine, Chiang Mai University (FAM-2560-05204), and the Department of Community Medicine and Global Health at the University of Oslo-Norwegian Centre for Research Data (58542).